Understanding Figurative languageat the Eighth Semester Students of English Language Education Study Program - Fibri Indira Lisanty (Journal of English Education, 2019)
The aim of this research is to know the Students’ Abilityin understanding Figurative language at the eight year students of English language education study program of UNCP. This study focuses on figurative testing specially in metaphor test. Quantitative descriptive method is the research design that the researcher used in this research. The population in this research was the eight year students of English Language Education Study Program,and sample in this research was 30 students. The ability of students is verypoor that the mean score was 32.67 which is classified into “low level” score category.